Noun-noun compounding in Esahie - Broohm, O. N; Marfo, C. O. (Linguistics Association of Ghana, 2024)
Noun-noun (N-N) compounds have been argued to constitute the commonest and most productive category of compounds cross-linguistically (cf. Downing 1977; Clark et al. 1985; Bauer 2017; Gagné & Spalding 2010; Guevara & Scalise 2009) and this fact is well-established in Kwa languages as well (cf. Akan: Appah (2013), Lɛtɛ: Akrofi Ansah (2012), Ewe: Agbadah (2017), and Dangme: Lawer (2017), Lawer & Appah (2020)). However, the subject remains to be explored as far as Esahie, which also belongs to the Kwa group of languages, is concerned. This paper, therefore, examines the form and function of N-N compounds in Esahie, from a Construction Morphology (Booij 2010) perspective. Among other things, the study reveals that subordinate compounds are predominantly right-headed, while attributive compounds are predominantly left-headed, and that the former is the most productive compounding type. Our findings on Esahie noun-noun compounds corroborate Booij’s (1992) observation that there is a strong correlation between recursion and productivity. Furthermore, we show that semantic headedness (rather formal headedness) provides the most reliable criterion for determining headedness in Esahie N-N compounds. Data is collected through documentary fieldworks conducted in Esahie-speaking communities of the Western North Region of Ghana.